Probabilistic slope stability analysis on marine clay seabed considering spatial variability of soil parameters - Yu, Long; Bao, Yang; Ma, Kunming; Han, Yunrui; Yan, Yibin; Xu, Bin; Wang, Zhongtao; Pang, Rui (Frontiers in Built Environment, 2025)
Determining the failure probabilities of submarine slopes over long distances is crucial for assessing slope stability, given the randomness of soil parameters. Based on the theory of stochastic fields and the method of limit equilibrium, this study introduces a quantitative method that incorporates spatial variability of soil parameters to evaluate submarine slope stability. Assuming a linear increase in undrained strength with depth, the slope stability is estimated under static loading derived from nonstationary random fields, and the effect of a weak layer on the slope stability is also analyzed. This study show that ignores the spatial variability of the soil parameters significantly overestimate the performance for the slope stability. In conclusion, the lower and upper ends of the probability index range are found to have great significance in practical engineering design. The combination of traditional deterministic slope analysis and probabilistic assessments will be beneficial to slope engineering practice and will improve the decision-making process.